Peptide-based enteral formula vs a whole protein enteral formula after major intestinal surgeries in children - Mohamed Saber Mostafa; Yasmin Gamal; Mohamed H. Soliman (SpringerOpen, 2021)
Abstract Background Malnutrition is a common finding after major abdominal surgeries especially after prolonged period of fasting in children. Enteral feeding is the commonest support way postoperatively for stimulating gut hormones, modulating immunity, and maintaining the barrier function of the intestinal mucosa. Our aim was to compare the results and outcome regarding tolerance, nutritional status, and hospital stay following a postoperative diet of peptide-based enteral formula against a whole protein enteral formula after major intestinal surgeries in pediatric patients who had resection and re-anastomosis after intussusception. Results This is a prospective cohort study on two groups of patients with a total of 30 patients during the period between January 2019 and June 2020. All patients in both groups underwent major intestinal surgeries (resection and re-anastomosis after intussusception). The first group received postoperative whole protein formula exclusively on the 3rd postoperative day while the other group received peptide-based formula exclusively on the same day. Postoperative mean serum albumin and pre-albumin levels were significantly higher in peptide-based formula group compared to those who had protein-based formula as their initial feeds (P value < 0.05). The average hospital stay was also significantly shorter in the peptide group (P value < 0.05). Peptide formula was easily tolerated than protein formula in postoperative children who had major intestinal surgeries. Conclusion Peptide-based enteral formulas are better tolerated and more useful as regards nutritional status than whole-protein formulas in post-operative course of pediatric patients regarding clinical outcome and better economically with shorter hospital stay.